Cutting Machine Manufacturing Design Process - Mikhael Sianipar, Binsar; Pradana, Sigit; Prayitno, Sugeng; Hadi Suryo, Taufik (PT Mattawang Mediatama Solution, 2023)
On development, technology created For make it easy work man. In the process of making potato sticks , the cutting process is still done manually using simple cutting tools and human power. This counts less effective in terms of time, security, as well as capacity Which generated. Therefore it is necessary to make a potato stick cutting machine to help produce potatoes. So that this thesis takes the theme